Guidance Note on Health Care Worker Safety from HIV and Other Blood Borne Infections - Gold, Julian; Tomkins, Maggy; Melling, Phillip; Bates, Nicholas (World Bank, Washington, DC, 2013)
The safety of heath care workers (HCWs) who take care of people with HIV/AIDS and other infectious diseases is of paramount importance. Occupational transmission of blood borne infections is not regarded as a common problem in developed country settings, but this is not the case in resource poor countries where the incidence and impact of such exposures is under-reported and is now becoming appreciated as an important risk factor for HCWs. It is generally assumed that protection from occupational exposures requires expensive equipment which is not reasonable for resource poor healthcare services. However, appropriately designed education and training, in combination with relatively low-cost technologies have the potential for both reducing injuries and increasing the confidence of Healthcare workers in providing essential care for their patients.